Factors predictive of complicated appendicitis in children - Roushan, Chandra Prakash; Sah, Ganesh Kumar; Mandal, Prince; Koirala, Dinesh Prasad; Dahal, Geha Raj (International Surgery Journal, 2021)
Background: Clinical features of acute appendicitis are often overlapping with other abdominal pathology in children. This increases the risk of complicated appendicitis (CA). It is still difficult to identify CA preoperatively. The study aims to identify pre operative risk factors in children for CA. Methods: A prospective study was conducted in pediatric surgery unit of department of general surgery of a university hospital of Kathmandu, Nepal. All children up to 16 years diagnosed and operated for appendicitis were included in the study. Based on intraoperative findings and histopathological examination (HPE), patients were grouped in simple appendicitis (SA) and CA. Pre-operative clinical and laboratory variables of between simple and CA were compared. P£0.05 was considered as significant. Results: A total of 73 children were included out of which 61 (83.6%) had SA and 12 (16.4%) had CA. Mean age of participants was 12.8±2.9 years. More than half (64.4%) of the participants were male. The median duration of symptoms was 2 days. In bivariate analysis, gender, serum Na, duration of symptoms and rebound tenderness were significantly associated with severity of appendicitis. In multivariate analysis, rebound tenderness (OR-15.36) and duration of symptoms (OR-9.96) were found to be associated with CA. Conclusions: Male patients, rebound tenderness, longer duration of symptoms and hyponatremia can be used to predict CA. Duration of symptoms and rebound tenderness are independent risk factors for CA.